Organizational Commitment among the Employees of NGOs in Bangladesh: An Empirical Study - Kumar, Dhanonjoy; Hossain, Md. Zakir; Jebin, Aleya (American Journal of Trade and Policy, 2016)
Committed human resource is one of the most valuable and effective assets of an organization. Meyer and Allen (1993) have documented that organizational commitment as a leading factor impacting the level of achievement in many organizations. Commitment-based organizations believe that staff’s organizational commitment contributes to workforce stability and better customer service, hence increase business performance. This study investigates the organizational commitment of NGOs employees’ in Bangladesh. It focuses on the relative importance of organizational commitment and their impact on the overall organizational success. A total number of 120 employees from three selected NGOs located at different districts in Bangladesh have been interviewed for this study purpose. Data have been collected through structured questionnaire. While tackling the issue addressed in the study relevant statistical tools and techniques were applied at appropriate places. The researchers have tried to measure the organizational commitment through recognized three major elements like-affective commitment, continuance commitment and normative commitment. The study revealed that the level of organizational commitment relating to above mentioned elements is not satisfactory. It is also exposed that demographic variables like age, gender, education and working experiences seemed to affect the commitment of employees. Another noticeable outcome of the study is that the organizational commitment has a significant impact on selected NGOs operations in Bangladesh.